2017
DOI: 10.1002/smr.1923
|View full text |Cite
|
Sign up to set email alerts
|

Towards actionable visualization for software developers

Abstract: Abundant studies have shown that visualization is advantageous for software developers, yet adopting visualization during software development is not a common practice due to the large effort involved in finding an appropriate visualization. Developers require support to facilitate that task. Among 368 papers in SOFTVIS/VISSOFT venues, we identify 86 design study papers about the application of visualization to relieve concerns in software development. We extract from these studies the task, need, audience, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Technique: City Visualization and Scatter plot. In a previous study [12], we observed that most visualizations to support developers in monitoring performance used pixel-based techniques. These visualizations usually attempt to provide an overview of a significant amount of data to promote the detection of visual patterns that may signal anomalies in the performance of software systems.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Technique: City Visualization and Scatter plot. In a previous study [12], we observed that most visualizations to support developers in monitoring performance used pixel-based techniques. These visualizations usually attempt to provide an overview of a significant amount of data to promote the detection of visual patterns that may signal anomalies in the performance of software systems.…”
Section: Designmentioning
confidence: 99%
“…PerfVis is a tool to visualize software performance through immersive augmented reality. We characterize the context of PerfVis using a taxonomy proposed by Maletic et al [6] and Merino et al [12].…”
Section: Perfvis Overviewmentioning
confidence: 99%
“…The beneits of using suitable visual metaphors both for assisting with software exploration and for reducing the cognitive load is widely accepted [1,8]. Several visual metaphors have been proposed for representing static aspects of software (cf.…”
Section: Stage 2: Visualisation Of Software Metricsmentioning
confidence: 99%
“…Visualisation Techniques. Software visualisation techniques are widely used in program comprehension; see for instance the recent survey in [8] about existing software visualisation approaches. This survey highlights the number of visualisation tools for supporting developers' needs on dependency management.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation